Impact of zinc supplementation on male infertility: a systematic review - de Lima, Jean F.; Daniel, Natália V. S.; Pietro, Luciana (Brazilian Journal of Health and Biomedical Sciences, 2023)
Introduction: According to the World Health Organization (WHO), infertility is defined as a failure in fertilization without any use of a contraceptive method for at least 12 consecutive months, with the individual being of reproductive age and having an active sexual life, where male infertility has been assuming a prominent position.This condition is considered to beof high importance in the contemporary world. Objectives:To systematically review the literature on the impactof oral zinc supplementation on male infertility and to assess whether its intake exerts a therapeutic effect, based on the evaluation of seminal parameters, according to manuals publishedby the WHO. Methodology: A systematic review was carried out by means ofa search, in the English and Portuguese languages, for original articles in the Pubmed, Science Direct, Lilacs and Scieloscientific databases. Results: The intervention groups ranged from 18 to 77 individuals and the control groups ranged from 8 to 113 individuals. Regarding age, the average age of the participants in the studies was31 years. The daily dose of zinc administered in thetrials variedfrom 66mg to 500mg and its use time ranged from three to six months. In the end, 87.5% of the studies showed positive results on the sperm parameters evaluated after the intervention. Conclusion:The results weremainly attributed to the protective effect that the trace element provided, reducing the lipid peroxidation index of plasma membranes and improving DNA integrity, thus increasing the fertilization capacity.